Comparison of Four Office-based Procedures in Treatment of Inferior Turbinate Hypertrophy - Kesornsukhon, Naruwat (Journal of Health Science of Thailand, 2018)
A prospective clinical trial was carried out to compare the efficacy of submucosal non – temperature controlled radiofrequency tissue volume reduction (RFTVR), temperatue controlled radiofrequency tissue volume reduction (TCRFTVR), submucosal resection with microdebrider (SMRM) and carbondioxide (CO2) laser ablation in office - based treatment of chronic inferior turbinate hypertrophy. The study was done in Samut Sakhon Hospital between August 2004 and September 2008. In all, 120 symptomatic inferior turbinate hypertrophy patients were enrolled, randomized, and separated into 4 groups ( 30 for each groups ). All patients in each groups were operated in both sides of inferior turbinate with the same instruments. Visual analogue scales (VASs), turbinate size, saccharin transport time (STT) were used to evaluate and compare the result at pre-operative, 12th week and 24th weeks post-operative periods. Significant improvement was achieved by VAS scores and turbinate size for all procedures at both post-operative evaluation periods in comparison to preoperative finding, whereas there were no significantly different outcomes in comparison between each techniques. However, the CO2 laser impaired STT in comparison between pre-operative and 12th, 24th weeks post-operative conditions, but no significant changing was found for the residual three submucosal procedures. The SMRM required more instruments and operation time than other techniques. In this 24 weeks period study, RFTVR and TCRFTVR reportedly yielded identical results of treatment to SMRM and CO2 laser. The RFTVR procedure is cheaper and faster in operation than TCRFTVR whereas no different outcomes of treatment between both radiofrequency techniques. The study suspected RFTVR is appropiate for office - based treatment of inferior turbinate hypertrophy as it is easy to perform, less time consuming, with promising outcomes, yet without admission requirement and harmful complications.